Hippocampus is more vulnerable to neural damages induced by repeated sevoflurane exposure in the second trimester than other brain areas. (9th June 2020) - Chen, Bing; Liu, Yanjun; Cai, Yirong; Tang, Dan; Xu, Saihong; Gao, Po; Yu, Weifeng; Jiao, Yingfu; Li, Wenxian
Abstract: During the rapidly developing and sensitive period of the central nervous system (CNS), a harmful stimulus may have serious consequences. The effect of anesthetic exposure on the development of the offspring's CNS during pregnancy is still unclear and has been widely concerned. In the present study, we compared the susceptibility of the hippocampus with those of other brain regions in offsprings when the mother mice were exposed to repeated sevoflurane. We found that other than affecting motor sensation, emotion, or social behavior of offspring mice, repeated sevoflurane exposure induced significant memory deficiency. Compared with other brain regions, the hippocampus, which is the key component of the brain serving for learning and memory, was more vulnerable to repeated sevoflurane exposure. We also found that repeated sevoflurane exposure to mother mice could inhibit the axon development of hippocampal neurons. We also predicted that N6-methyladenosine modification of mRNA might play an essential role in the vulnerability of the hippocampus to sevoflurane, while the underlying cellular mechanism needs to be explored in the future. Our study may provide a new perspective for studying the mechanism of hippocampus-specific injury induced by sevoflurane exposure.